Kevin Kissell speaking to class - Unidentified photographer (Colorado State University. Libraries, 2016)
Photograph of faculty member Kevin Kissell speaking about a historic garment from the collection to his fashion illustration class at the Avenir Museum of Design and Merchandising in 2016. Kissell is standing next to a dressed mannequin positioned on a table. Students are seated in the foreground.
Keywords: Fashion -- History; Fashion -- Exhibitions